Analisis Wirausaha Bimbingan Belajar pada Program Wirausaha Merdeka - Hasrawati Ramli; Sri Hastati; Erwin Nurdiansyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Abstract: This research aims to find out the entrepreneurial planning of tutoring for the independent entrepreneurship program, to find out the implementation of entrepreneurship tutoring in the independent entrepreneurship program. This type of research, this research is categorized as a type of qualitative descriptive research. Researchers use qualitative descriptive research because the data obtained is in the form of words and language in a special, natural context and by utilizing various natural methods. The research design used in this research is the triangulation method in the form of observation, interviews and documentation. Based on the results of observations of planning activities and implementation of entrepreneurial tutoring in the independent entrepreneurship program. The samples in this research were fellow independent entrepreneurs and Ganesha Operation mentors in Makassar City. The results of this research show that the tutor's efforts help students overcome various learning problems carried out at home. The meaning of tutoring planning is to provide additional material to improve the learning outcomes of students who are classified as having difficulty understanding the lesson material presented by the teacher. The implementation of tutoring is carried out from house to house to help busy parents to provide learning facilities for their children by following tutoring. Regarding the curriculum used in this tutoring, it uses the latest curriculum developments that are relevant to learning in schools.